Polyisocyanurate-based polymers and fiber-reinforced composite materials
By using high-functional polyurethane and a small amount of epoxy resin in the polyurethane reaction mixture, and using a catalyst to promote the reaction, the problem that polyurethane materials in the prior art are difficult to have high strength, wear resistance and high glass transition temperature at the same time, and the preparation of high-performance polyurethane polymers is achieved.
Patent Information
- Application Number
- JP2021533590
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-12-11
- Filing Date
- 2019-12-11
- Publication Date
- 2025-05-07
- Estimated Expiration
- 2039-12-11
AI Technical Summary
The prior art is difficult to improve the wear resistance and heat resistance of the polyurethane reaction mixture while maintaining high strength, high fracture rate, high crack toughness and high glass transition temperature.
Using a multifunctional polyurethane reaction mixture, containing high-functional polyurethane and a small amount of epoxy resin, the reaction is promoted through a catalyst to form a high-performance polyurethane polymer.
The high strength, high fracture rate, high crack toughness and high glass transition temperature of polyurethane polymer are achieved, while improving the wear and heat resistance of the material, and curing can be completed in a lower temperature and in a short time.
Smart Images

Figure 0007671986000009 
Figure 0007671986000010 
Figure 0007671986000011
Abstract
Description
[Technical field]
[0001] The present invention relates generally to isocyanate reacting mixtures, and more particularly to isocyanate reacting mixtures containing polymeric methylene diphenyl diisocyanate (pMDI) that upon cure result in polymers having high strength, high strain to break, high fracture toughness, and high glass transition temperature. [Background technology]
[0002] Isocyanurates are formed by the trimerization of three isocyanates and have been widely used for decades to enhance the thermal stability of polyurethanes, epoxies, and polyureas. Isocyanurates are also widely used in the manufacture of foams due to their excellent flame retardancy, but high density polymers based essentially only on polyisocyanurates could not be used without forming additional bonds that serve to increase the toughness of the polymer. To overcome the widely known defect of polyisocyanurate foams as brittleness, polyisocyanurates have had to contain a high percentage of reactants that consume isocyanate groups and limit the percentage of isocyanurate in the polymer. For example, US Pat. No. 5,499,366 describes the use of "a foam formulation of 4 to 20% by weight of a surface active organosilicone compound characterized by active hydrogen functionality and having a hydroxyl number of about 50 or more and an equivalent weight of less than about 2,000, and a plasticizing amount of a non-volatile organic plasticizer" to reduce the abrasiveness of the foam. US Pat. No. 5,499,366 discloses the use of 1 to 10% of an aliphatic diol to form a polyurethane lineage that increases the elasticity of the polymer. US Patent No. 5,399,633 describes the trimerization of isocyanate-terminated polyoxazolidone prepolymers using a trimerization catalyst such as a tertiary amine. The inventors state that the resulting polymer exhibits low friction and high flame retardancy due to the incorporation of oxazolidone linkages. US Patent No. 5,399,633 discloses that foams with high crosslink density of pure polyisocyanurate have very brittle properties and are "of no practical value." The inventors use 10-50% epoxy resin to obtain reduced brittleness.
[0003] It is widely known that when polyisocyanurates are used to make dense plastics with low void content, the material becomes brittle unless they incorporate linear bonds, chain extenders, or flexible groups that act to increase toughness, i.e., oxazolidones as disclosed in US Pat. No. 5,399,414; US Pat. No. 5,633,663; and US Pat. No. 5,731,636; urethanes as disclosed in US Pat. No. 5,399,431; and ureas as disclosed in US Pat. No. 5,731,663. For example, US Pat. No. 5,731,663 teaches that cured isocyanate / epoxy blends with epoxy to isocyanate ratios less than 1:5 are very brittle and get worse with increasing diphenyl diisocyanate concentration (MIDI), and US Pat. No. 5,731,663 teaches that polyisocyanurates with less than 20% epoxy show deterioration in mechanical properties. These two patents teach that polymers with high strength and toughness cannot be obtained with less than 20% epoxy resin or less than 20% oxazolidones, which are the result of the reaction of isocyanate with epoxy at high temperatures. Furthermore, U.S. Patent No. 5,399,633 teaches that "materials made from polyisocyanurates are known to be very difficult to toughen, and some are too brittle to be effectively toughened," and that "attempts in the past to increase fracture toughness have often come at the expense of changing (generally decreasing) the modulus and decreasing the thermal properties, e.g., the glass transition temperature (Tg), thereby creating unacceptable limitations in the applicability of the resulting composite material."
[0004] US Patent No. 5,399,633 teaches that the molar ratio of at least one epoxy resin to at least one isocyanate resin should be at least 0.4:1, and most preferably 1:1, which ratio provides "particularly advantageous properties in terms of glass transition temperature, modulus and impact resistance." These preferred ratios far exceed the catalytic amount of epoxy to obtain the desired tensile strength, tensile stiffness and tensile strain to break. Moreover, the above mentioned patents clearly teach that polymers and foams consisting essentially of polyisocyanurates exhibit a high degree of brittleness.
[0005] Patent Document 16 discloses a method for preparing an oxazolidone / isocyanurate polymer in which the epoxy to isocyanate ratio is less than 1, and points out that the most advantageous epoxy to isocyanate ratio is in the range of 0.29 to 0.5, which results in a high glass transition temperature and good mechanical properties. Patent Document 16 discloses that "the isocyanurate bond portion having a high crosslink density and the relatively flexible portion based on the epoxide are present together, so that a moderate balance is maintained between the two portions, and a cured product with excellent mechanical properties can be obtained." The inventors state that "When the polyfunctional organic isocyanate is 5 equivalents or more, the properties of the cured product tend to become significantly brittle. In particular, when the polyfunctional organic isocyanate is used in the range of 2 to 3.5 equivalents, good results are obtained in terms of thermal stability and mechanical performance." US Patent No. 5,399,663 discloses that the inventors evaluated the polymers of US Patent No. 5,399,663 with a specified range of epoxy to isocyanate ratios and found that "subject to the given crosslinking conditions, extremely brittle oxazolidone / isocyanurate molding materials were obtained, with mechanical properties becoming worse with increasing concentrations of diphenylmethane diisocyanate (MDI)." The inventors claim that to obtain polymers with good mechanical properties, one should mix 1 to 5 parts epoxy to isocyanate. This disclosure refutes the idea that a large proportion of oxazolidone is necessary to achieve polymers with high strength, high strain at break, high fracture toughness and high glass transition temperature, and demonstrates that cured compositions consisting essentially of isocyanurate crosslinks can provide excellent mechanical properties when polymeric methylene diphenyl diisocyanate (pMDI) is included in the reaction mixture along with catalytic amounts of epoxy.
[0006] Oxazolidones are used in important applications due to their high thermal stability, but are not suitable for all applications because their formation requires high temperatures, generally above 150°C. Polyurethanes are common chemicals in the development of rigid plastics as well as coatings, adhesives, sealants and elastomers (CASE), formed by the reaction of hydroxyls with isocyanates, with most polymers formed from the reaction of diols or polyols with diisocyanates or polyisocyanates. When trimerization is desired, this chemical is often used to form prepolymers or is incorporated into the reaction mixture to reduce the weight percent of isocyanates (designated NCO) in the reaction mixture, resulting in cured compositions exhibiting improved elasticity and toughness, but generally at the expense of Young's modulus and glass transition temperature (Tg). US Pat. No. 5,399,633 teaches that it is generally preferred to cure in the presence of one or more polyols with an upper limit of 10:1 isocyanate to polyol ratio, i.e., an isocyanate index of 10. US Patent No. 5,399, 667 discloses the use of polymeric MDI with phenolic novolac resins in a concentration ratio to pMDI of 2:1 to 10:1, preferably 3:1 to 7:1, to produce a formaldehyde-free wood adhesive. US Patent No. 5,399, 667 teaches that pMDI requires a high proportion of phenolic novolac resin to form a high strength polymer with high toughness. Both of these patents teach that urethane linkages are necessary to obtain a cured composition with acceptable mechanical properties.
[0007] Numerous patents focus on the formation of oligomeric prepolymers with terminal isocyanate groups that can subsequently react with molecules containing active hydrogen to form dense polymers. US Pat. No. 5,399,433 discloses prepolymerization of an isocyanate blend of MDI isomers and polymeric MDI to form a partially trimerized isocyanurate polymer, which is then reacted with a polyol to reduce the friability of the isocyanurate foam. US Pat. No. 5,399,433 discloses a storage stable liquid partially trimerized polyisocyanate having an NCO group content of 24-40% by weight, containing 20-88% by weight TDI and 12-80% by weight MDI. US Pat. No. 5,399,433 discloses a process for the preparation of mixed trimers by at least partially trimerizing the isocyanate groups of two isocyanate components having different reactivities (with respect to trimerization) in the presence of a trimerization catalyst, and the mixed trimers prepared by this process. Patent Document 22 describes a storage-stable liquid polyisocyanate having an NCO group content of 36.5-45% and prepared by mixing 25-70 parts of partially trimerized 2,4-TDI with 75-30 parts of unmodified 2,4- and / or 2,6-TDI. These documents disclose a number of methods for producing isocyanurate prepolymers of aromatic, aliphatic, and blended aromatic and aliphatic structures, but none of the documents discloses a curing composition prepared essentially by the reaction of an isocyanate.
[0008] Another approach to the preparation of polyisocyanurate polymers exhibiting increased fracture toughness is the preparation of prepolymers containing amide, imide, urea, urethane, allophanate or biuret linkages, followed by trimerization of the isocyanate-terminated prepolymer. US Pat. No. 5,399,433 and US Pat. No. 5,499,443 disclose allophanate-modified toluene diisocyanurates having an NCO group content of about 15 to about 42%. These compositions are prepared by reacting A) toluene diisocyanate and B) an organic compound containing at least one hydroxyl group in the presence of a catalytic amount of C) at least one allophanate-trimer catalyst, or under an allophanate-trimer catalyst system. These compositions contain both isocyanurate groups and a high percentage of allophanate groups, and also contain urethane groups. However, these patents do not teach the subsequent reaction of the allophanate-modified toluene diisocyanurates with themselves or other isocyanate-terminated monomers, oligomers, prepolymers or polymers to form cured compositions.
[0009] US Pat. No. 5,399,663, US Pat. No. 5,499,826, and US Pat. No. 5,499,833 describe forming a trimerized prepolymer and then reacting the remaining free isocyanate with a monofunctional active hydrogen compound or mixtures thereof to produce polyurethanes containing isocyanurate trimers. There is ample literature on forming an isocyanurate-containing prepolymer that is subsequently reacted with an active hydrogen-containing molecule, or trimerizing an isocyanurate-terminated prepolymer prepared with a urethane, urea, allophanate, amide, biuret, or oxazolidones, but these reaction mixtures all require an active hydrogen compound to form a cured composition, and therefore, a urethane, amide, urea, biuret, or allophanate reaction product is utilized to form the cured composition. The present invention discloses a cured composition produced from a reaction mixture consisting essentially of an isocyanate-terminated monomer, oligomer, or prepolymer or polymer to form a cured composition.
[0010] Patent document 28 describes a composite material based on polyisocyanurate and containing a reinforcing filler, the polyisocyanurate matrix having the following formula: [ka] The repeating structural unit isocyanurate having the formula:
[0011] wherein at least one radical X represents a -R1-NCO group and at least one radical X represents a radical -R1-NH-CO-OR2-(-OCO-NH-R1-NCO)n, n being an integer between 1 and 8, preferably between 1 and 3, R1 being an aliphatic, cycloaliphatic, aromatic or mixed radical containing up to 20 carbon atoms, R2 being the same as or different from R1 and being an aliphatic, cycloaliphatic, aromatic or mixed radical containing up to 20 carbon atoms, or being a carbonic, siloxane, silane or corresponding mixed radical, the composite material can in particular be obtained by the following process: According to a preferred embodiment, in the repeating structural unit of formula (I), on average two radicals X represent a -R1-NCO group and the third radical X represents the radical -R1-NH-CO-OR2-(-OCO-NH-R1-NCO)n. The prepolymer formed is thus a polyurethane prepolymer in which at least 33% of the links are polyurethane chains. Also, the inventors explicitly describe isocyanurate-modified polyurethanes, since they state that "an essential feature of the composite materials of the present invention is the process by which they are obtained, which involves the use of specific prepolymers prepared by partial addition of polyisocyanates and polyols that remain fluid at room temperature." Patent Document 28 does not teach curing compositions that consist essentially of isocyanurates or that include reinforcing fillers.
[0012] Patent document 29 relates to a fiber composite component produced by impregnating a fiber with a reaction resin mixture of polyisocyanate, polyol, trimerization catalyst and optional additives, and a method for producing the same. The inventors teach that the ratio of the number of isocyanate groups to the number of OH groups is 1.6 to 6.0, in particular 2.1 to 3.5. Patent document 29 also discloses that the reaction mixture is preferably free of epoxy resins, but does not teach a polymer substantially composed of reaction products of isocyanate with itself, i.e. isocyanurates, uretdiones, carbodiimides and open structures.
[0013] US Patent No. 30 discloses that thermosetting resins based on polyisocyanate and urethane chemistry are not widely used in filament winding because the mixing of activated components requires a precise combination of two or more chemical precursors such as polyisocyanate and polyol with a well-defined stoichiometry. The problem with mixing activated components is that the reaction is difficult to control because the reaction may occur upon contact even at ambient temperature without the use of a catalyst and the reaction rate is difficult to control.
[0014] The above-mentioned prior art documents disclose various approaches to reacting various active hydrogen-containing molecules to improve the physical properties of polymers, including polyisocyanurates, but none of the documents provide a cured composition produced by the reaction that is essentially free of the reaction products of these moieties and that provides the high strength, stiffness, high strain at break, high toughness, and high glass transition temperature required for modern polymers, fiber reinforced polymers, and adhesives. [Prior art documents] [Patent documents]
[0015] [Patent Document 1] U.S. Pat. No. 4,568,701 [Patent Document 2] U.S. Pat. No. 3,676,380 [Patent Document 3] U.S. Pat. No. 3,793,236 [Patent Document 4] China Patent Application Publication No. 103,012,713 [Patent Document 5] U.S. Pat. No. 8,501,877 [Patent Document 6] US Patent Application Publication No. 2010 / 0151138 [Patent Document 7] European Patent No. 226,176 [Patent Document 8] European Patent Application Publication No. 0,643,086 [Patent Document 9] U.S. Pat. No. 9,334,379 [Patent Document 10] U.S. Patent No. 6,617,032 [Patent Document 11] Chinese Patent No. 103,568,337 [Patent Document 12] U.S. Pat. No. 4,564,651 [Patent Document 13] U.S. Pat. No. 5,036,135 [Patent Document 14] European Patent Application Publication No. 3,189,088 [Patent Document 15] US Patent Application Publication No. 2018 / 0051119 [Patent Document 16] U.S. Pat. No. 4,070,416 [Patent Document 17] U.S. Pat. No. 9,816,008 [Patent Document 18] U.S. Patent No. 6,294,117 [Patent Document 19] U.S. Pat. No. 4,382,125 [Patent Document 20] U.S. Patent No. 6,515,125 [Patent Document 21] U.S. Pat. No. 4,518,761 [Patent Document 22] U.S. Pat. No. 4,456,709 [Patent Document 23] U.S. Patent No. 6,028,158 [Patent Document 24] U.S. Patent No. 6,063,891 [Patent Document 25] U.S. Pat. No. 4,359,550 [Patent Document 26] U.S. Pat. No. 3,817,939 [Patent Document 27] U.S. Pat. No. 4,359,541 [Patent Document 28] European Patent No. 226,176 [Patent Document 29] U.S. Pat. No. 9,334,379 [Patent Document 30] US Patent Application Publication No. 2005 / 0038222 Summary of the Invention [Means for solving the problem]
[0016] In one embodiment, the method for making an isocyanurate polymer provides a liquid aromatic polyisocyanurate in which less than about 10% by weight of an epoxy resin is mixed into the liquid aromatic polyisocyanurate. In another embodiment, after providing less than about 10% by weight of an epoxide resin, the liquid aromatic polyisocyanurate is mixed with a catalyst composition. The aromatic polyisocyanurate includes a polymeric methylene diphenyl diisocyanate (pMDI) that provides an aromatic polyisocyanurate with an average functionality greater than 2 to form a reaction mixture. In one embodiment, the pMDI includes a blend of MDI and a higher functionality pMDI. The mixture is cured at a temperature greater than about 70° C. to produce a polymer composition that includes the reaction product of two or more isocyanates. In another embodiment, the mixture is aged at ambient temperature and pressure to improve performance.
[0017] Prior art literature indicates that reaction mixtures using high proportions of pMDI or other aromatic polyisocyanurates generally result in poor performance polymers that are too brittle for practical use. The chemical compositions of the present invention refute these assertions and provide unexpected performance results that exceed all other polyisocyanurate mixtures. Surprisingly, the glass transition temperatures of the resulting thermoset polymers are well above 300°C, levels previously unattainable with polyisocyanurates.
[0018] Surprisingly, it has been discovered that aging the polymer in a humid, atmospheric pressure and temperature environment results in an isocyanurate polymer with a significantly increased glass transition temperature (Tg). Furthermore, the presence of an aliphatic isocyanurate (trimer) or uretdione (dimer) in the reaction mixture has been shown to provide a more complete cure and reduce the temperature required to obtain a high strength polymer. It has also been found that, in accordance with the present invention, the polymer can be cured in less than 5 minutes, resulting in mechanical properties equivalent to those of polymers cured for longer times and at higher temperatures. [Brief description of the drawings]
[0019] Other advantages of the present invention will be readily appreciated as the same becomes better understood by reference to the following detailed description when considered in connection with the accompanying drawings.
[0020] [Figure 1] FIG. 1 is the DMA measurements for Example 10 after heat curing and after the sample was left at ambient temperature, pressure and humidity for 90 days. [Diagram 2] FIG. 2 shows the DMA measurements for Example 21 after aging for 60 days at ambient temperature and humidity in an environmentally controlled laboratory. [Diagram 3] FIG. 3 shows the DMA measurements of Example 12 after heat curing and after the cured sample was placed in a 100% humidity, 40° C. environment for 72 hours. [Figure 4]FIG. 4 is the DMA measurements of Example 9 after heat curing and after immersion of the cured sample in 80° C. water for 24 hours. [Diagram 5] FIG. 5 shows the DMA measurements of carbon fiber composite Example 24 after aging for 65 days at ambient temperature and humidity in an environmentally controlled laboratory. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] The present invention has found that polymerization of a liquid reaction mixture containing polymeric methylene diphenyl diisocyanate (pMDI) results in a cured (hardened) composition with high strength, glass transition temperature, Young's modulus and toughness, while the reaction mixture is substantially free of chemicals that provide chain extenders during cure, such as oxazolidones, amides, urethanes and ureas. As further described herein below, by selecting an appropriate catalyst, the cured compositions of the present invention can be obtained at 120°C in 5 minutes or less, and at 140°C or greater in 2.5 minutes or less, providing heretofore unobtainable results. In the present invention, dense polymers are those that are substantially free of voids, with a void content of less than 10%, or even less than 2%. In the present invention, high toughness (0.5 MPa·m 1 / 2 High molecular weight (MgO) and molecular weight (MnO2) are achieved by polymerization of a reaction mixture containing polymeric methylene diphenyl diisocyanate and a catalytic amount of epoxy, while being substantially free of molecules containing active hydrogen sites such as hydroxyl, primary and secondary amines, carboxylic acids, thiols, etc., known to those skilled in the art. The present invention further shows that, contrary to expectations, the presence of aliphatic uretdiones, aliphatic trimers, or aliphatic iminooxadiazinediones (which are reaction mixtures of two or three aliphatic isocyanates) accelerates the polymerization reaction, allowing for greater isocyanate conversion and improved mechanical strength at lower cure temperatures.
[0022] The present invention provides, in one embodiment, a method for producing a polymeric composition cured by polymerization of isocyanate groups, the method comprising the steps of:
[0023] (1) providing a liquid reaction mixture, the liquid reaction mixture comprising: A) at least one liquid, aromatic polyisocyanate, and B) optionally at least one liquid, aliphatic polyisocyanate; C) catalyst composition; Including, The at least one aromatic polyisocyanate comprises polymeric methylene diphenyl diisocyanate (pMDI), such that the at least one aromatic polyisocyanate has a functionality greater than 2, in particular at least 2.2, or at least 2.5, or even greater than 2.65. Furthermore, the reaction composition comprises at least one epoxide, which may be monofunctional or polyfunctional, in a proportion of up to 7.5% by weight, in particular 0.01% to 5%, in another embodiment 0.5% to 4%, in another embodiment 1.0% to 3%, and in yet another embodiment 2% of the total reaction mixture.
[0024] (2) curing the reaction mixture by self-reaction of the isocyanate groups to obtain a cured polymer composition comprising structures that are reaction products of isocyanates with themselves.
[0025] In a further aspect, the present invention relates to a cured composition containing a filler to improve the mechanical properties of the cured composition, the filler being in one embodiment a continuous fiber and in another embodiment a discontinuous fiber.
[0026] As used herein, "at least one" refers to one or more, e.g., 1, 2, 3, 4, 5, 6, 7, 8, 9 or more. For the components of the catalyst composition described herein, this information refers to the type of component, not the absolute amount of the molecule. Thus, for example, "at least one epoxy resin" means one or more different epoxy resins, i.e., one or more different types of epoxy resins. Together with the amount, the amount refers to the total amount of the correspondingly identified type of component, as previously defined.
[0027] As used herein, "liquid" refers to a composition that is flowable at room temperature (20° C.) and normal pressure (1,013 mbar).
[0028] When referring to a chemical moiety, "substantially free" means that the mole fraction of molecules containing the specified moiety is less than 7.5% in the reaction mixture or cured composition. In some cases, "substantially free" means that the mole fraction of molecules containing the specified moiety is less than 5% in the reaction mixture or cured composition. Conversely, "substantially" and "essentially" mean that the mole fraction of molecules containing the specified moiety is greater than 92.5% of the reaction mixture or cured composition. In some cases, "substantially" and "essentially" mean that the mole fraction of molecules containing the specified moiety is greater than 95% of the reaction mixture or cured composition.
[0029] The viscosity of the liquid compositions described herein is particularly low enough that the composition is pumpable and capable of wetting and impregnating fibrous materials, such as those used in fiber-reinforced plastic parts. In various embodiments, the reaction mixture has a viscosity of <2,500 mPa·S at room temperature and <150 mPa·S at a temperature of 50° C. To determine the viscosity, a resin mixture is prepared at room temperature using a suitable mixer and the viscosity is determined with a spindle-type rheometer.
[0030] The present invention provides a cured composition having high strength, high fracture toughness, and high glass transition temperature by curing a reaction mixture consisting essentially of polyisocyanates, where at least one polyisocyanate is polymeric methylene diphenyl diisocyanate (pMDI), such that the reaction mixture has a functionality greater than 2, particularly at least 2.2, in another embodiment at least 2.5, and in a further embodiment greater than 2.7. Curing the reaction mixture with a trimerization catalyst comprising at least one epoxy results in a hard polymer, which is essentially an isocyanurate polymer with high tensile strength (greater than 50 MPa), high toughness (0.5 MPa·m 1 / 2 The cured compositions essentially of polyisocyanurates exhibit fracture toughness and strength that are lacking unless a small amount of polymeric methylene diphenyl diisocyanate (pMDI) is used in the reaction mixture to produce an isocyanate functionality of greater than 2, particularly at least 2.2, more preferably at least 2.5, and even more preferably greater than 2.65. In the prior art, epoxies are known to improve the fracture toughness of polymers, but the present invention includes an amount of epoxy that represents a catalyst and therefore does not significantly affect the material properties.
[0031] Oligomeric MDI in the sense of the present application means a polyisocyanate mixture of higher nuclear homologues of MDI having at least three aromatic nuclei and a functionality of at least 3. The terms "polymeric diphenylmethane diisocyanate", "polymeric MDI" and "oligomeric MDI" are used within the context of the present invention to refer to a mixture of oligomeric MDI and optionally monomeric MDI. Generally, the monomer content of polymeric MDI ranges from 25 to 85 wt.%, based on the total mass of pMDI, such that the average functionality is greater than about 2.1.
[0032] In addition to pMDI, the isocyanate mixture of step 1) may also contain monomeric or oligomeric or prepolymeric isocyanates. Monomeric isocyanates include the customary aliphatic, cycloaliphatic and aliphatic di- and / or polyisocyanates known from polyurethane chemistry, in particular aromatic isocyanates. Aromatic isocyanates, in particular isomers of the MDI series (monomeric MDI) and TDI, are particularly useful.
[0033] Isocyanates useful in the embodiments disclosed herein include isocyanates, polyisocyanates, isocyanate carbodiimides, uretdiones, and trimers containing such isocyanates. Suitable polyisocyanates include any of the aromatic, aliphatic, cycloaliphatic, cycloaliphatic, and araliphatic di- and / or polyisocyanates known in the art. These isocyanates include variants such as uretdiones, isocyanurates, carbodiimides, and iminooxadiazinediones, particularly those formed by the reaction of isocyanates with each other.
[0034] Suitable aromatic diisocyanate compounds may include, for example, xylylene diisocyanate, meta-xylylene diisocyanate, tetramethylxylylene diisocyanate, tolylene diisocyanate, 4,4'-diphenylmethane diisocyanate, 1,5-naphthalene diisocyanate, 1,4-naphthalene diisocyanate, 4,4'-toluidine diisocyanate, 4,4'-diphenylether diisocyanate, m- or p-phenylene diisocyanate, 4,4'-biphenylene diisocyanate, 3,3'-dimethyl-4,4'-biphenylene diisocyanate, bis(4-isocyanatophenyl)-sulfone, isopropylidenebis(4-phenylisocyanate), and the like. Polyisocyanates having three or more isocyanate groups per molecule may include, for example, triphenylmethane-4,4',4"-triisocyanate, 1,3,5-triisocyanatobenzene, 2,4,6-triisocyanatotoluene, 4,4'-dimethyldiphenylmethane-2,2',5,5'-tetraisocyanate, and the like. Aliphatic polyisocyanates may include, for example, hexamethylene diisocyanate, 1,4-diisocyanatobutane, 1,8-diisocyanatooctane, m-xylylene diisocyanate, p-xylylene diisocyanate trimethylhexamethylene diisocyanate, dimer acid diisocyanate, lysine diisocyanate, and the like. and uretdione-type adducts, carbodiimide adducts, and isocyanurate ring adducts of these polyisocyanates. The alicyclic diisocyanates may include isophorone diisocyanate, 4,4'-methylenebis(cyclohexylisocyanate), methylcyclohexane-2,4- or -2,6-diisocyanate, 1,3- or 1,4-di(isocyanatomethyl)cyclohexane, 1,4-cyclohexane diisocyanate, 1,3-cyclopentane diisocyanate, 1,2-cyclohexane diisocyanate, and the like, and uretdione-type adducts, carbodiimide adducts, and isocyanurate ring adducts of these polyisocyanates.
[0035] In a further embodiment of the invention, the reaction mixture comprises 15-85% polymeric MDI, 15-85% isomers and homologs of diphenylmethane diisocyanate. In another embodiment of the invention, the reaction mixture comprises 15 to 85% polymeric MDI, 25-65% isomers and homologs of diphenylmethane diisocyanate, and 2-20% uretdione of hexamethylene diisocyanate. In another embodiment of the invention, the reaction mixture comprises 15-85% polymeric MDI, 25-65% isomers and homologs of diphenylmethane diisocyanate, and 2-20% trimer of hexamethylene diisocyanate.
[0036] Surprisingly, the cured composition formed in step 2) of the present invention achieves greater isocyanate conversion when the reaction mixture includes an aliphatic uretdione, an aliphatic isocyanurate, or an aliphatic iminooxadiazinedione, and the cured composition can achieve high mechanical properties at a lower reaction temperature than in their absence. This result is unexpected since aliphatic isocyanates are known to react slower than aromatic isocyanates, but provide increased reactivity in the reaction mixture of step 1). Uretdiones, isocyanurates, carbodiimides, and iminooxadiazinediones are reaction products of two or three isocyanates as shown below, where x, x', and x" are the same or different aliphatic lineages with terminal isocyanate groups. [ka]
[0037] Of course, mixtures of any of the above isocyanates may also be used. Furthermore, there are many different orders for contacting or combining the compounds required to form the polyisocyanurate containing reaction mixtures of the present invention. Those skilled in the art will appreciate that blends and variations in the order of addition of the compounds are within the scope of the present invention.
[0038] (Catalyst composition) The reaction mixture is cured via a catalyst composition that induces trimerization of the polymer. The trimerization catalyst can include amine catalysts such as N,N-dimethylbenzylamine (BDMA), 4-dimethylaminopyridine (DMAP), 2-dimethylaminopyridine (2-DMAP), 1,4-diazabicyclo[2.2.2]octane (DABCO), bis-(2-dimethylaminoethyl)ether (BDMAEE), 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU), 1,5-diazabicyclo[4.3.0]non-5-ene (DBN), N-alkylmorpholines, N-alkylalkanolamines, tris(dimethylaminopropyl)hexahydrotriazines, N,N-dialkylcyclohexylamines, alkylamines where the alkyl groups are methyl, ethyl, propyl, butyl and isomers thereof, heterocyclic amines, and the like. Amine catalysts also include quaternary ammonium hydroxides and quaternary ammonium salts, such as benzyltrimethylammonium hydroxide, benzyltrimethylammonium chloride, benzyltrimethylammonium methoxide, (2-hydroxypropyl)trimethylammonium 2-ethylhexanoate, (2-hydroxypropyl)trimethylammonium formate, etc. In one embodiment, BDMA, in another embodiment, BDMAEE, in another embodiment, DABCO, dissolved in a suitable solvent, such as benzene, benzonitrile, tetrahydrofuran, nitrobenzene, or other suitable solvent known to those skilled in the art, is used in the catalyst composition at a weight of 0.001 to 10 wt%, more preferably 0.1 to 3 wt%. In another embodiment, the catalyst may be used as a solvent for DABCO, and suitable catalyst solvents include BDMA, imidazole, organometallic compounds, or other catalysts capable of solvating DABCO known to those skilled in the art, used in the catalyst composition at a weight of 0.001 to 10 wt%, more preferably 0.1 to 3 wt%.
[0039] Non-amine catalysts can also be used. Organometallic compounds of bismuth, lead, tin, potassium, lithium, sodium, titanium, iron, antimony, uranium, cadmium, cobalt, thorium, aluminum, mercury, zinc, nickel, cerium, molybdenum, vanadium, copper, manganese, and zirconium can be used. Examples include potassium acetate, potassium naphtholate, potassium octoate, potassium 2-ethylhexanoate, bismuth nitrate, lead 2-ethylhexanoate, lead benzoate, ferric chloride, antimony trichloride, stannous acetate, stannous octoate, stannous 2-ethylhexanoate, and the like.
[0040] In other embodiments, suitable catalysts include imidazole compounds including compounds having one imidazole ring per molecule, such as imidazole, 2-methylimidazole, 2-ethyl-4-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 2-ethylimidazole, 2-isopropyl ... Benzyl imidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-isopropylimidazole, 1-cyanoethyl-2-phenylimidazole, 2,4-diamino-6-[2'-methylimidazolyl-(1)']-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4-methylimidazolyl-(1)']-ethyl- s-Triazine, 2,4-diamino-6-[2'-undecylimidazolyl-(1)']-ethyl-s-triazine, 2-methylimidazolium-isocyanuric acid adduct, 2-phenylimidazolium-isocyanuric acid adduct, 1-aminoethyl-2-methylimidazole, 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2-phenyl-4-benzyl-5-hydroxymethylimidazole, etc. and compounds having two or more imidazole rings per molecule obtained by dehydrating the above-mentioned hydroxymethyl-containing imidazole compounds, such as 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, and 2-phenyl-4-benzyl-5-hydroxymethylimidazole, and condensing these compounds by a deformaldehyde reaction, such as 4,4'-methylene-bis-(2-ethyl-5-methylimidazole).
[0041] Optionally, a latent catalyst such as that described in US Pat. No. 5,999,633 can be used to slow down the curing reaction. Such latent catalysts are known to those skilled in the art and are commonly used in the preparation of prepregs, sheet molding compounds (SMC) and bulk molding compounds (BMC). In one embodiment not disclosed in the prior art, 2-(dimethylamino)pyridine acts as the latent catalyst.
[0042] In another embodiment of the present invention, the catalyst comprises at least one epoxy resin cocatalyst. The behavior of epoxy resin cocatalysts is described in US Pat. No. 2,979,485. Epoxy resins can include epoxide group-containing monomers, prepolymers, polymers and mixtures thereof, hereinafter also referred to as epoxides or epoxide group-containing resins. Suitable epoxide group-containing resins are in particular resins containing 1 to 10, or 1 to 2, or 1 epoxide group per molecule. As used herein, "epoxide group" means 1,2-epoxide group (oxirane). Preferably, at least one epoxy is added to the reaction mixture in an amount of 0.1 to 10 wt. %, or 0.5 to 3 wt. % by weight of the reaction mixture. The epoxy acts as a cocatalyst, but may be added to the reaction mixture separately from the trimerization catalyst. In one embodiment, the epoxy is essentially mixed with the reaction mixture of the isocyanurate to form a storage-stable mixture that can later be catalyzed.
[0043] The reaction mixture is mixed with a catalyst composition and cured by trimerization to produce a 500 kg / m 3 , preferably 1000kg / m 3 The curing reaction is preferably carried out at elevated temperatures of 50-200° C., or 75-170° C., or even 80-150° C. In one embodiment of the invention, the reaction mixture is mixed with a catalyst composition and cured to form a cured composition consisting essentially of a reaction product between two or more isocyanates, including an imide.
[0044] Trimerization of isocyanurates is known to be a slow process, especially in the absence of solvent, but the present invention allows for surprisingly fast curing. The present invention shows that the reaction mixture can be cured in less than 5 minutes at 120°C, or in less than 2.5 minutes at temperatures above 140°C, while achieving mechanical properties (see Examples 17-23) equivalent to those cured for longer times (see Example 11). Rapid polymer curing is required for high volume manufacturing industries such as the automotive industry, where polymerization in less than 10 minutes is required. The unexpectedly rapid cure also achieves high strength, stiffness, and toughness. In one embodiment of the present invention, the reaction mixture can be cured in 2 minutes or less, and in another embodiment, the reaction mixture can be cured in 90 seconds or less. In another embodiment of the present invention, the reaction mixture can be cured in less than 60 seconds. The rate of reaction is controlled by the catalyst concentration and is greatly accelerated by the presence of an epoxy or epoxide included as a co-catalyst that reacts with the trimerization catalyst to form the composite. The higher the ratio of epoxy to trimerization catalyst, the faster the polymerization rate. Surprisingly, it has been found that the reaction mixture according to the invention remains stable for a significant period of time until the temperature rises above 70° C., after which curing occurs very rapidly. Furthermore, the reaction is less exothermic than other fast curing resins (e.g., vinyl esters, epoxies, polyesters, etc.), allowing the processing of thicker materials.
[0045] Unexpectedly, the cured composition continues to cure over time, even in some cases in the presence of humidity or moisture around the sample, to achieve a glass transition temperature of greater than 250°C, or greater than 300°C, or greater than 325°C, or greater than 340°C. The rate of this final cure reaction is determined by the temperature and humidity of the environment around the cured composition. When the cured composition is exposed to humidity levels typical of a climate-controlled building, e.g., 22°C and 20-70% relative humidity, the final reaction is complete in 2-12 weeks, or alternatively, 4-8 weeks. Figure 1 shows the storage modulus and tan δ measured by dynamic mechanical analysis (DMA) of Example 10 after 90 days aging, demonstrating a significant improvement in glass transition temperature. Figure 2 shows the storage modulus and tan δ measured by dynamic mechanical analysis (DMA) of Example 21 after aging for 60 days in an ambient environment, demonstrating a significantly improved glass transition temperature from 195.5°C after curing to 354.2°C after 60 days at ambient atmospheric conditions. FIG. 2 demonstrates that samples cured for less than 5 minutes show an unexpected increase in Tg, as do samples cured for longer periods. However, as shown in the DMA measurements of FIG. 3, at 40° C., atmospheric pressure, and 100% relative humidity, the reaction is complete in 24-72 hours, or 24 hours. The aging reaction conditions can be varied, with higher humidity and temperature allowing for more rapid curing. With reference to FIG. 1, a DMA measurement of Example 10 is shown after thermal curing and exposing the sample to ambient temperature, pressure, and humidity for 90 days, as further described below. After the aging period, the glass transition temperature (Tg) increases from 196° C. to 356° C. This result is completely unexpected based on the teachings of the prior art. With further reference to FIG. 3, a DMA measurement of Example 12 is shown after thermal curing and exposing the cured sample to an ambient environment of 40° C. and 100% humidity for 72 hours, as further described herein below. The glass transition temperature (Tg) increases from 185° C. to 345° C., another unexpected result.
[0046] In additional embodiments, the cured composition can be immersed in water to complete the reaction and obtain a glass transition temperature of greater than 250°C, or greater than 300°C, or greater than 325°C, or greater than 340°C. The rate of reaction is believed to depend on the temperature and pressure of the water. For example, immersion of a sample in 80°C results in complete cure in less than 48 hours, or less than 24 hours. Thermomechanical properties measured by dynamic mechanical analysis (DMA) are shown in Figure 4 for Example 9 after heat curing and immersion of the thermoset polymer in water at 80°C at atmospheric pressure for 24 hours. The glass transition temperature (Tg) is measured from the peak of the Tan δ curve and shows an increase in Tg from 240°C to 374°C after immersion in water. While many polymers experience a decrease in glass transition temperature after absorbing moisture, the present invention shows a dramatic increase in glass transition temperature. 4, as described in more detail herein below, shows DMA measurements of Example 9 after heat curing and immersion of the cured sample in water at 80° C. and atmospheric pressure for 24 hours. After immersion in water, the glass transition temperature (Tg) increases from 240° C. to 374° C.
[0047] In one embodiment of the present invention, the reaction mixture is blended with continuous or discontinuous reinforcing fibers and cured with a trimerization catalyst composition to form a fiber reinforced molded part. Such molded parts are useful in the construction of automobiles, wind turbines, sporting goods, aerospace structures, pressure vessels, building materials, and printed circuit boards. However, the end use of the fiber reinforced plastic molded part can be adapted for other applications as known to those skilled in the art.
[0048] Known high-strength fiber materials suitable as fiber components for fiber-reinforced cured compositions include, for example, synthetic fibers such as carbon fibers, glass fibers, polyester fibers, polyethylene fibers, polypropylene fibers, polyamide fibers, polyimide fibers, polyoxazole fibers, polyhydroquinone diimidazopyridine fibers, aramid fibers, oxidizing or non-oxidizing ceramic fibers such as boron fibers, aluminum oxide / silicon dioxide fibers, silicon carbide fibers, metal fibers, for example made of steel or aluminum, or natural fibers such as flax, hemp, or jute. These fibers can be introduced in the form of mats, woven fabrics, knitted fabrics, laid scrims, nonwoven fabrics, rovings. It is also possible to use a mixture of two or more of these fiber materials. Such high-strength fibers, laid scrims, woven fabrics, and rovings are known to those skilled in the art.
[0049] In particular, the fibre composite should contain fibres in a volume percentage of more than 25 vol.%, or more than 50 vol.%, or between 50 and 70 vol.%, based on the total fibre composite, in order to obtain particularly good mechanical properties.
[0050] The reactive mixture may be blended with reinforcing fibers by known methods such as, for example, resin transfer molding (RTM), vacuum assisted resin transfer molding (VARTM), injection molding, high pressure reaction injection molding (HP-RIM), wet lay-up, pultrusion, or prepreg techniques. The present invention is particularly suited to injection because it is a liquid at room temperature.
[0051] In various embodiments of the invention, depending on the desired application, the reactive mixture is applied to a substrate, for example when used as an adhesive, or loaded into a molding tool, when used as a molding compound for producing plastic parts. In one embodiment, the method is a resin transfer molding (RTM) method and the reactive mixture is a reactive injection resin. "Reactive" as used in this context means that the injected resin can be chemically crosslinked. In the RTM method, providing the reactive mixture, i.e. step (1) of the described method, can include injecting, in particular injecting, the injected resin into a molding tool. In the case of producing fiber-reinforced plastic parts, for which the described method and reactive mixture are particularly suitable, fibers or semi-finished fiber products (prewoven / preforms) can be placed in the molding tool before injection. The fibers and / or semi-finished fiber products used can be materials known for this application in the prior art, in particular carbon fibers.
[0052] In one embodiment of the invention, the reactive mixture is injected by resin transfer molding into a mold containing continuous or discontinuous fibers and cured in less than 5 minutes. In another embodiment of the invention, the reactive mixture is injected by resin transfer molding into a mold containing continuous or discontinuous fibers and cured in less than 2 minutes. In another embodiment of the invention, the reactive mixture is injected by resin transfer molding into a mold containing continuous or discontinuous fibers and cured in less than 1 minute.
[0053] In one embodiment of the invention, the reaction mixture is injected into a wind turbine blade mold containing continuous or discontinuous fibers by resin transfer molding and cured at a temperature below 95°C. In another embodiment of the invention, the reaction mixture is applied to the continuous fibers by direct injection or placed in a resin bath and pultruded through a heated die. In either of these embodiments, a catalyst is blended into the reaction mixture just prior to processing. It should also be appreciated that the compositions of the invention are particularly suited for pultrusion as they are fast curing, in less than 5 minutes, and in another embodiment, in less than 2 minutes.
[0054] Like the cured composition, fiber reinforced composites prepared with the cured composition also increase in Tg upon environmental aging. Figure 5 shows the storage modulus and tan δ measured by dynamic mechanical analysis (DMA) for Example 24 after 65 days of aging, demonstrating a significant improvement in glass transition temperature from 209.3°C to 335.1°C, a level previously thought unattainable.
[0055] In one embodiment of the invention, the reaction mixture contains sufficient adhesive properties to be used as an adhesive. The reaction mixture may be compounded with fillers known as adhesives, such as fumed silica, glass beads, ceramic particles, nanowires, nanorods, nanoparticles, carbon nanotubes (CNTs), synthetic particles such as rubbers, elastomers, or thermoplastics.
[0056] In a further embodiment of the invention, the cured composition is flame retardant. In another embodiment of the invention, the cured composition is non-flammable.
[0057] The present invention achieves a cured composition consisting essentially of isocyanurate crosslinks with excellent mechanical properties without the use of high curing temperatures or expensive chemical compounds. Moreover, the present invention results in polymers with very high glass transition temperatures. Moreover, the present invention shows that the presence of aliphatic uretdiones, aliphatic trimers, or aliphatic iminooxadiazinediones in the reaction mixture promotes the trimerization reaction, resulting in greater isocyanurate conversion, whereas the general expectation is that the presence of aliphatic components reduces reactivity. Moreover, the present invention shows that the polymerization reaction can be completed in a few minutes, resulting in polymers compatible with mass production.
[0058] (Example) Polyisocyanurate polymers were prepared in the following manner: Monomeric MDI was used as a liquid blend of methylene diphenyl diisocyanate (MDI) isomers under the tradename MONDOUR MLQ from Covestro and LUPRANATE MI from BASF, the blend consisting essentially of a 50 / 50 blend of 4,4'-MDI and 2,4'-MDI. Polymeric methylene diphenyl diisocyanate (pMDI) under the tradename LUPRANATE M20 from BASF is composed of less than 55% oligomeric MDI, 38% monomeric 4-4 diphenylmethane diisocyanate, less than 10% MDI isomers, and has an average isocyanate functionality of 2.7 according to the material's MSDS. Polymeric methylene diphenyl diisocyanate (pMDI) was obtained from Covestro under the trade name MONDUR MR Light, which according to Covestro's MSDS for the material is composed of 58% oligomeric MDI, 38% monomeric 4-4 diphenylmethane diisocyanate, 3.8% 2,4'-MDI, and 0.2% 2,2'-MDI with an average isocyanate functionality of 2.8. HDI uretdione was obtained from Covestro under the trade name DESDODUR N3400, and HDI trimer was obtained from Wanhua under the trade name Wannate HT-100. Technical grade toluene diisocyanate (80% tolylene-2,4'-diisocyanate) was obtained from Sigma Aldrich at 80% purity, and all chemicals were used as received. EPON was obtained from Hexion. TM Bisphenol A / epichlorohydrin based bifunctional liquid epoxy resin stock solutions sold under the trade name 828 and EPON from Hexion TMThe diglycidyl ether of bisphenol F sold under the trade name 862, monofunctional reactive diluents glycidyl phenyl ether (GPE) obtained from TCI America in greater than 99% purity, and cresyl glycidyl ether (CGE) obtained from Evonik under the trade name Epodil 742, were used. N-benzyldimethylamine (BDMA) was obtained from Alfa Aesar in greater than 98% purity, 1,4-diazabicyclo[2.2.2]octane (DABCO) was obtained from TCI Chemicals in greater than 98% purity, bis-(2-dimethylaminoethyl)ether (BDMAEE) was obtained from Huntsman International under the trade name ZF-20, and stannous octoate was obtained from Sigma Aldrich in 92.5-100.0% purity. No special storage or handling procedures were used for these reagents, and no further purification was performed.
[0059] (Neat resin sample preparation) The selected isocyanate for the chosen formulation was mixed using a vortex mixer and the catalyzed epoxy was added to the solution. The mixture was mixed for an additional minute using a Fisher vortex mixer. The catalyst was then added to the mixture at the desired concentration and mixed for 1 minute using a vortex mixer. The solution was then centrifuged for 2 minutes at 5,000 rpm in a centrifuge to remove any air that was entrapped during mixing. Other common methods can be used to degas the sample (i.e., vacuum pressure, sonication). The solution was then carefully added to a silicone rubber mold made by Ellsworth Adhesives using a XIAMETER® RTV-4230-E Silicone Rubber Kit. The mold containing the reaction mixture was placed in an autoclave, pressurized to 100 psig, heated to the desired temperature, held at this temperature for the desired time, and then cooled to room temperature. The cured sample was cooled under pressure until the temperature of the autoclave dropped below 80° C., and the cured polymer was removed from the autoclave. Samples that were cured in less than 10 minutes were prepared by heating the silicone mold before adding the catalyst (catalyzed) reaction mixture and then placing it in the autoclave, which was then rapidly closed, pressurized, and vented so that the cured polymer could be removed from the autoclave within the prescribed cure time. The test specimens were immediately removed from the mold.
[0060] (Fracture toughness) Samples for measuring the fracture toughness of neat resins were prepared according to ASTM Standard D5045 - Plain Strain Toughness Testing of Polymers, specifically following the "notched beam" geometry. A Buehler ECOMET 3 variable speed grinder-polisher was used to remove surface defects and ensure that the specimens conformed to the geometric tolerances set by the test standard. Precracks were created using a slit saw on a CNC milling machine, after which the crack tips were sharpened by sliding the sample over a fixed unused razor blade a minimum of 10 times. The razor blade was changed for each sample specimen, and a fixture was used to ensure that the crack tips were sharpened uniformly. The precracked samples were loaded in a three-point bend test apparatus mounted on an Instron 3367 test frame equipped with a 30 kN load cell. The maximum load before the crack propagated through the sample was recorded and used to calculate the fracture toughness. Means and standard deviations were calculated based on sample sets of at least five specimens.
[0061] (Tensile test piece) Samples for measuring the tensile strength and stiffness of the neat resin were prepared according to ASTM Standard D638, specifically using Type IV geometry. Samples were removed from the silicone rubber mold and polished to specifications using a Buehler ECOMET 3 variable speed grinder polisher. The sides were hand sanded using commercial grade sandpaper and finally polished using 1500 grit wet / dry sandpaper. Specimens were mounted in Instron 50kN wedge grips attached to a 30kN load cell within an Instron 3367 testing frame. A failure mode analysis was performed to ensure proper and expected failure of the material occurred during testing and to ensure failure of the gauge section. The maximum load during testing was recorded and used to calculate the tensile strength, the initial slope of the stress-strain curve was used to calculate the tensile modulus, and the crosshead elongation was used to calculate the strain to failure for each specimen. Means and standard deviations were calculated based on sample sets of at least five specimens.
[0062] (Water bath treatment) Neat resin samples were prepared as described above. After removal from the autoclave and removal of the mould, they were immersed in a bath of RO filtered water. The bath was loosely covered and placed in an oven at 80°C for 24 hours. After that, the bath was removed from the oven and the samples were taken out of the bath after cooling. The corresponding sample preparation procedure was then followed to prepare the samples for testing.
[0063] (humidity treatment) Neat resin samples were prepared as described above. After they were removed from the autoclave and demolded, the specimens were placed in a saturated humidity environment. This environment was created by placing excess liquid water on a Pyrex tray in a laboratory vacuum oven. The oven was heated to 40°C and completely sealed from the outside environment so that the water evaporated into the air and remained there. The humidity inside the oven was maintained at approximately 100%. The samples were left in this environment for 24-72 hours. Similar tests were performed at atmospheric pressure in a laboratory environment controlled to 22°C and 20-70% relative humidity.
[0064] Ambient Aging: Samples were aged in a climate-controlled laboratory. Relative humidity was not controlled.
[0065] Dynamic Mechanical Analysis: The glass transition temperature (Tg) of the cured polymer and fiber reinforced polymer composites was measured using dynamic mechanical analysis (DMA), and Tg was identified as the peak of Tan δ cure.
[0066] Comparative examples were prepared to demonstrate some of the embodiments of the present invention. Tables 1, 3 and 4 show the components of the reaction mixture and the reaction conditions. All example reactions were prepared according to the procedure for the neat resin test samples.
[0067] (Examples 1 to 9) The formulations and cure conditions for Examples 1-9 are shown in Table 1, and the corresponding material properties for all Examples are shown in Table 2. Tensile strength, tensile stiffness, and break strain were determined according to ASTM D638 using a Type IV geometry, and fracture toughness was measured according to ASTM 5045 using single edge notched beam specimens. Comparative Examples 1-9 demonstrate cure conditions of 180°C for 12 hours, showing that polymers with high mechanical strength, stiffness, and toughness can be achieved using various combinations of reactants. Table 2 shows the glass transition temperatures of the specimens after 12 weeks of aging at ambient conditions, showing that very high Tg can be achieved.
[0068] [Table 1]
[0069] [Table 2]
[0070] (Examples 10 to 23) The formulations and cure conditions for Examples 10-16 are shown in Table 3, the formulations and cure conditions for Examples 17-22 are shown in Table 4, and the material properties for all Examples are shown in Table 5. Tensile strength, tensile stiffness, and break strain were measured using Type IV geometry according to ASTM D638, and fracture toughness was measured using single edge notched beam specimens according to ASTM 5045. Comparative Examples 10-16 demonstrate that low temperature cure conditions can result in cured compositions, and Comparative Examples 17-22 demonstrate that cured compositions with high performance properties can be obtained in less than 5 minutes. Comparative Example 10 includes an isocyanurate of hexamethylene diisocyanate (Wannate HT-100) and Comparative Example 11 includes a uretdione of hexamethylene diisocyanate (DESMODUR N3400) cured at 85°C for 2 hours, showing that excellent mechanical properties are obtained, whereas Comparative Example 12 omits the aliphatic component and, under the same curing conditions, results in a brittle polymer with limited strength. Aliphatic isocyanates are known to be less reactive than aromatic isocyanates, and therefore the presence of an aliphatic component in the reaction mixture would be expected to slow the reaction. This comparative example shows that, contrary to expectations, the presence of an aliphatic component allows the polymer to be cured at a lower temperature. This result is further demonstrated by Examples 13 and 14, cured at 110°C and 120°C for 2 hours, respectively, showing that mechanical properties improve with increasing reaction temperature and similar properties can be obtained without the presence of an aliphatic isocyanate in the reaction mixture at 120°C. Comparative Example 15 shows the use of DABCO dissolved in BDMA in a weight ratio of 1:5 as a catalyst, while Comparative Example 16 shows that mechanical properties can be further improved by increasing the curing temperature. Comparative Examples 17 and 18 show that the reaction mixture of the present invention can be cured in as little as 5 minutes while achieving similar mechanical properties as those cured at lower temperatures for longer periods. Examples 19-23 use a catalyst solution of DABCO dissolved in a suitable solvent. Examples 19-23 use a solution of DABCO:benzonitrile in a weight ratio of 1:3.Comparative Examples 19 and 20 demonstrate that the reaction mixture of the present invention can be cured in as little as 3 minutes while achieving mechanical properties equivalent to those cured at lower temperatures for longer periods. Example 21 demonstrates that the reaction mixture of the present invention can be cured in as little as 2 minutes at 160°C while achieving mechanical properties equivalent to those cured at lower temperatures for longer periods. Example 22 demonstrates that the reaction mixture can be cured in 5 minutes at 120°C while achieving mechanical properties equivalent to those cured at higher temperatures, and Example 23 demonstrates that the reaction mixture can be cured in 3 minutes at 130°C while achieving mechanical properties equivalent to those cured at higher temperatures.
[0071] Example 24 This was demonstrated by injecting the reaction mixture into fibrous reinforcement to create fiber reinforced composite specimens. Vacuum assisted resin transfer molding (VARTM) was employed to inject the reaction mixture from Example 20 into 8 plies of 12k Mitsubishi Grafil carbon fiber unidirectional carbon tape with a light weight of 373 gsm. The VARTM process was completed for 2-10 minutes before the panels were cured in an autoclave at 100 psi, 170°C for 3 minutes, or in a hot press at 170°C for 3 minutes. After inserting the composite into the autoclave, it was sealed and immediately pressurized until it reached 100 psi, approximately 90 seconds after the vacuum bagged composite was placed in, and then the pressure was held for approximately 15 seconds, after which the autoclave door was opened and vented to allow removal of the composite at temperature after 180 seconds. After removal from the autoclave, the cured composite was immediately removed from the plate and vacuum bag and allowed to cure at ambient conditions. This process was designed to simulate the High Pressure Resin Transfer Molding (HP-RTM) process, and demonstrated that cold resin can be cured in 3 minutes, whereas in high pressure injection systems the resin can be heated before being introduced into the mold, greatly accelerating the cure. The short beam strength of this composite was tested according to ASTM 2344 and showed a high short beam strength of 69.0 ± 3.68 MPa.
[0072] [Table 3]
[0073] [Table 4]
[0074] [Table 5]
[0075] In one embodiment of the present invention, the cured composition significantly increases its glass transition temperature upon aging in the presence of atmospheric moisture or when immersed in water. Table 6 shows the glass transition temperature (Tg) of selected examples before and after aging at ambient pressure and humidity, at high temperature and humidity, and after immersion in hot water. In each example, the results show that the glass transition temperature of the cured composition is significantly improved. Prior art polymers primarily exhibit a decrease in glass transition upon exposure to moisture. However, the cured composition of the present invention has a significantly increased glass transition temperature, as shown in Table 6 below. This result is quite surprising and contrary to conventional teachings.
[0076] [Table 6]
[0077] Obviously, many modifications and variations of the present invention are possible in light of the above teachings, and the foregoing invention has been described in accordance with the relevant legal standards, and thus, the description is merely exemplary rather than limiting in nature. Variations and modifications of the disclosed embodiments will become apparent to those skilled in the art and may fall within the scope of the invention. Thus, the scope of legal protection given to this invention can only be determined by studying the following claims.
[0078] [Note] [Appendix 1] 1. A method for producing an isocyanurate-based polymer, comprising the steps of: Providing a liquid aromatic polyisocyanurate; Providing a catalyst composition; forming a reaction mixture, the aromatic polyisocyanurate comprising a combination of methylene diphenyl diisocyanate (MDI) and polymeric methylene diphenyl diisocyanate (pMDI) to provide an average functionality of greater than 2, the catalyst composition comprising a trimerization catalyst and at least one epoxide, the epoxide being mono- or polyfunctional, and curing the reaction mixture to produce a polymer composition comprising the reaction product of two or more isocyanates; Including, A method for producing an isocyanurate polymer.
[0079] [Appendix 2] The step of providing said aromatic polyisocyanurate having a functionality greater than 2 is further defined by providing said aromatic polyisocyanurate having an average functionality greater than about 2.5. The method according to claim 1,
[0080] [Appendix 3] Uretdione providing an aliphatic polyisocyanate of hexamethylene diisocyanate comprising at least one of an isocyanurate, a biuret, an allophanate, or an iminooxadiazinedione; The method described in Appendix 1.
[0081] [Appendix 4] The catalyst composition comprises a monofunctional or polyfunctional epoxide in an amount of up to about 7% by weight based on the total reaction mixture. The method according to claim 1,
[0082] [Appendix 5] The epoxide is present in an amount of about 3% by weight based on the total reaction mixture. The method according to claim 1,
[0083] [Appendix 6] the reaction mixture is substantially free of reactive hydrogen and the cured composition is substantially free of urethane and amide groups; The method according to claim 1,
[0084] [Appendix 7] the reaction mixture is further defined by an isocyanate-terminated prepolymer comprising at least one of a urethane group, an amide group, a urea group, a uretdione group, a biuret group, an allophanate group, an isocyanurate group, or a carbodiimide group; The method according to claim 1,
[0085] [Appendix 8] The reaction mixture contains 5 to 20% by weight of at least one of a uretdione of hexamethylene diisocyanate and a trimer of hexamethylene diisocyanate. The method according to claim 1,
[0086] [Appendix 9] The polymer composition is post-cured in either a wet environment or an aqueous solution to provide a glass transition temperature of greater than 300° C. The method according to claim 1,
[0087] [Appendix 10] aging the polymer composition at ambient temperature and pressure in an environment containing atmospheric moisture, thereby providing the polymer composition with a glass transition temperature greater than about 300° C. The method according to claim 1,
[0088] [Appendix 11] The polymer composition achieves a glass transition temperature of greater than about 350° C. after environmental aging. The method according to claim 1,
[0089] [Appendix 12] providing a fibrous material and injecting the fibrous material into a reaction mixture, the reaction mixture being performed after catalyzing the reaction mixture and prior to heating the reaction mixture to cure the fiber reinforced composite material reaction mixture; The method according to claim 1,
[0090] [Appendix 13] 2. The method of claim 1, wherein the at least one epoxide is mixed with the reaction mixture prior to providing the trimerization catalyst, thereby forming a storage stable mixture for subsequent catalysis with the trimerization catalyst.
[0091] [Appendix 14] The reaction product has a viscosity of about 0.5 MPa m according to ASTM standard D5045. 1 / 2 The method of claim 1, wherein the material has a fracture toughness greater than or equal to 100%.
[0092] [Appendix 15] 2. The method of claim 1, wherein the step of curing the reaction product is further defined by thermally curing the reaction mixture in less than 10 minutes.
[0093] [Appendix 16] said step of curing said reaction product is further defined by thermally curing said reaction mixture at less than 120° C. for less than 5 minutes. The method according to claim 1,
[0094] [Appendix 17] said step of curing said reaction product is further defined by thermally curing said reaction mixture at less than 170° C. for less than 2 minutes. The method according to claim 1,
[0095] [Appendix 18] said step of curing said reaction product is further defined by thermally curing said reaction mixture at less than 170° C. for less than 1 minute. The method according to claim 1,
[0096] [Appendix 19] The liquid aromatic polyisocyanurate has a viscosity of less than 1,500 mPa·s. The method according to claim 1,
[0097] [Appendix 20] The liquid aromatic polyisocyanurate has a viscosity of less than 300 mPa·s. The method according to claim 1,
[0098] [Appendix 21] wherein said step of providing a fibrous material is further defined by providing at least one of unidirectional glass fiber, woven glass fiber, non-crimped glass fiber, non-woven glass fiber, unidirectional carbon fiber, woven carbon fiber, non-crimped carbon fiber, non-woven carbon fiber, unidirectional basalt fiber, woven basalt fiber, non-bonded basalt fiber, non-woven basalt fiber, and the like. The method according to claim 1,
[0099] [Appendix 22] 1. A method for producing an isocyanurate polymer material, comprising: Providing aromatic polyisocyanates including methylene diphenyl diisocyanate (MDI) and polymeric methylene diphenyl diisocyanate (pMDI); mixing a catalytic amount of an epoxy with the aromatic polyisocyanate to form a reactive blend; After preparing the reactive blend, mixing a catalyst with the reactive blend to initiate polymerization of the isocyanurate polymer material and heating the reactive blend to less than about 170° C. for less than 5 minutes, thereby curing the isocyanurate polymer material; The method includes:
[0100] [Appendix 23] said step of combining a catalyst with said reaction blend is further defined by combining a trimerization catalyst with said reaction blend. 23. The method of claim 22,
[0101] [Appendix 24] wherein said step of mixing a catalyst into said reaction blend is further defined by mixing at least one of bis-(2-dimethylaminoethyl) ether (BDMAEE) or 1,4-diazabicyclo[2.2.2]octane (DABCO) dissolved in a suitable solvent into said reaction blend. 24. The method according to claim 23,
[0102] [Appendix 25] wherein said step of mixing a catalytic amount of an epoxy with said aromatic polyisocyanurate is further defined by mixing less than about 10% by weight of an epoxy with said aromatic polyisocyanurate. 23. The method of claim 22,
[0103] [Appendix 26] providing a fibrous material and injecting the fibrous material into the catalyzed reacting blend prior to heating the reacting blend. 23. The method of claim 22,
[0104] [Appendix 27] wherein said step of providing a fibrous material is further defined by providing at least one of unidirectional glass fiber, woven glass fiber, non-crimp glass fiber, non-woven glass fiber, unidirectional carbon fiber, woven carbon fiber, non-crimp carbon fiber, non-woven carbon fiber, unidirectional basalt fiber, woven basalt fiber, non-crimp basalt fiber, non-woven basalt fiber, and the like; 27. The method according to claim 26,
[0105] [Appendix 28] The polyisocyanurate polymer is defined by being substantially free of reactive hydrogen, urethane groups and amide groups. 23. The method of claim 22,
[0106] [Appendix 29] wherein said step of heating said reactive blend is further defined by curing said isocyanurate polymer material by heating said reactive blend at less than 120° C. for less than 5 minutes. 23. The method of claim 22,
[0107] [Appendix 30] The polymer composition has a glass transition temperature of greater than 300° C. after aging at ambient temperature and pressure. 23. The method of claim 22,
Claims
1. 1. A method for producing an isocyanurate-based polymer, comprising the steps of: Providing a liquid aromatic polyisocyanate; Providing a catalyst composition; forming a reaction mixture, the aromatic polyisocyanate comprising a combination of methylene diphenyl diisocyanate (MDI) and polymeric methylene diphenyl diisocyanate (pMDI) to provide the aromatic polyisocyanate with an average functionality of greater than 2; and the catalyst composition comprising a trimerization catalyst and at least one epoxide, which is mono- or polyfunctional; curing the reaction mixture to produce a polymer composition comprising a reaction product between two or more isocyanates; Including, the reaction mixture is substantially free of reactive hydrogen and the cured composition is substantially free of urethane and amide groups; 1. A method for producing an isocyanurate polymer, comprising the steps of:
2. The step of providing said aromatic polyisocyanate having a functionality greater than 2 is further defined by providing said aromatic polyisocyanate having an average functionality greater than 2.
5.
2. The method of claim 1 .
3. providing an aliphatic polyisocyanate of hexamethylene diisocyanate comprising at least one of a uretdione, an isocyanurate, a biuret, an allophanate, or an iminooxadiazinedione; 2. The method of claim 1 .
4. The catalyst composition comprises a monofunctional or polyfunctional epoxide in a proportion of up to 7% by weight based on the total reaction mixture; 2. The method of claim 1 .
5. The epoxide is present in an amount of 3% by weight based on the total reaction mixture.
2. The method of claim 1 .
6. the reaction mixture is further defined by an isocyanate-terminated prepolymer comprising at least one of a urethane group, an amide group, a urea group, a uretdione group, a biuret group, an allophanate group, an isocyanurate group, or a carbodiimide group; 2. The method of claim 1 .
7. the reaction mixture comprises 5 to 20 weight percent of at least one of a uretdione of hexamethylene diisocyanate and a trimer of hexamethylene diisocyanate; 2. The method of claim 1 .
8. providing a fiber material and injecting the fiber material into a reaction mixture, the reaction mixture being performed after catalyzing the reaction mixture and prior to heating the reaction mixture to cure the fiber material and the reaction mixture; 2. The method of claim 1 .
9. 2. The method of claim 1 , wherein the at least one epoxide is mixed into the reaction mixture prior to providing the trimerization catalyst, thereby forming a storage stable mixture for subsequent catalysis with the trimerization catalyst.
10. The reaction product has a viscosity of 0.5 MPa m according to ASTM standard D5045. 1/2 2. The method of claim 1, wherein the composite has a fracture toughness greater than 0.
1.
11. 10. The method of claim 1, wherein the step of curing the reaction mixture is further defined by thermally curing the reaction mixture in less than 10 minutes.
12. said step of curing said reaction mixture is further defined by thermally curing said reaction mixture at less than 120° C. for less than 5 minutes.
2. The method of claim 1 .
13. said step of curing said reaction mixture is further defined by thermally curing said reaction mixture at less than 170° C. for less than 2 minutes.
2. The method of claim 1 .
14. said step of curing said reaction mixture is further defined by thermally curing said reaction mixture at less than 170° C. for less than 1 minute.
2. The method of claim 1 .
15. The reaction mixture has a viscosity of <2,500 mPa·S at room temperature and <150 mPa·S at a temperature of 50° C.
2. The method of claim 1 .
16. the step of providing a fiber material is further defined by providing at least one of unidirectional glass fiber, woven glass fiber fabric, non-crimped glass fiber, non-woven glass fiber fabric, unidirectional carbon fiber, woven carbon fiber fabric, non-crimped carbon fiber, non-woven carbon fiber fabric, unidirectional basalt fiber, woven basalt fiber fabric, non-bonded basalt fiber, and non-woven basalt fiber fabric; 9. The method of claim 8.
17. 1. A method for producing an isocyanurate polymer, comprising the steps of: Providing aromatic polyisocyanates including methylene diphenyl diisocyanate (MDI) and polymeric methylene diphenyl diisocyanate (pMDI); mixing a catalytic amount of an epoxy with the aromatic polyisocyanate to form a reactive blend; After preparing the reaction blend, mixing a catalyst with the reaction blend to initiate polymerization of the aromatic polyisocyanate and heating the reaction blend at less than 170° C. for less than 5 minutes, thereby curing the aromatic polyisocyanate and obtaining an isocyanurate polymer; Including, the reactive blend being defined by being substantially free of reactive hydrogen and the isocyanurate polymer being substantially free of urethane and amide groups. A method comprising:
18. said step of combining a catalyst with said reaction blend is further defined by combining a trimerization catalyst with said reaction blend.
20. The method of claim 17 .
19. wherein said step of mixing a catalyst into said reaction blend is further defined by mixing at least one of bis-(2-dimethylaminoethyl)ether (BDMAEE), or 1,4-diazabicyclo[2.2.2]octane (DABCO), dissolved in a suitable solvent, into said reaction blend.
20. The method of claim 18 .
20. said step of mixing a catalytic amount of an epoxy with said aromatic polyisocyanate is further defined by mixing less than 10 weight percent of an epoxy with said aromatic polyisocyanate; 20. The method of claim 17 .
21. providing a fibrous material; and injecting the fibrous material into the catalyzed reacting blend prior to heating the reacting blend.
20. The method of claim 17 .
22. wherein the step of providing a fiber material is further defined by providing at least one of unidirectional glass fiber, woven glass fiber, non-crimp glass fiber, non-woven glass fiber, unidirectional carbon fiber, woven carbon fiber, non-crimp carbon fiber, non-woven carbon fiber, unidirectional basalt fiber, woven basalt fiber, non-crimp basalt fiber, and non-woven basalt fiber.
22. The method of claim 21 .
23. wherein the step of heating the reaction blend is further defined by curing the aromatic polyisocyanate by heating the reaction blend to less than 120° C. for less than 5 minutes.
20. The method of claim 17 .
Citation Information
Patent Citations
High-strength high temperature resistant epoxy modified polyisocyanurate foamed plastic and preparation method thereof
CN103012713A
Preparation method for contact moulded polyurethane or polyurea composite material member
CN103568337A
EP0,643,086
Polyisocyanate composition
EP0447093A2
EP226,176